DETERMINAN SOLVABILITAS DANA TABARRU’ PADA PERUSAHAAN ASURANSI SYARIAH DI INDONESIA - Lestari, Iis Indah; Mukhibad, Hasan (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
AbstractSolvency of tabarru’ funds can indicate a company's ability to pay obligations Islamic insurance claims payments to the participants or policyholders. Related to this, the Financial Services Authority has set a minimum limit of solvency margin tabarru’ funds which amounted to 30% which must be fulfilled by Islamic insurance companies. However, there are three Islamic insurance companies that have a solvency tabarru’ funds under the terms of at least 30%, such as PT Asuransi Astra Buana, Takaful Protection Jaya and PT Tugu Pratama Indonesia. The purpose of this study was to determine the effect of firm size, type of company, Retakaful premiums, investment, wealth available to qardh, and operating expenses to fund solvency tabarru on Islamic insurance company in Indonesia. The population in this study was Islamic insurance company over registered at the Financial Services Authority (OJK) in the year 2013-2018. By using purposive sampling techniques, sample end of the study amounted to 14 mining companies with 84 units of analysis. Meanwhile, the analysis used descriptive statistical analysis and panel regression analysis with Eviews 9. The results showed that the return on investment and wealth available to qardh positive and significant impact on the solvency of tabarru’ fund. Variable size of company, type of company, Retakaful premiums, and operating expenses partially have no effect on the solvency of the tabarru’ fund.